NEGARA UTAMA MENURUT AL-FARABI (KONSEP DAN RELEVANSINYA DALAM KEHIDUPAN BERNEGARA MASA KINI) - Mutiani, Tika (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This reseach to find of understand the views of Islamic political philosopher Al-Farabi on the main country (al-madinah al-fadhilah). This method used of analysis description. This result reseach The country that is the mainstay of Medina is the State of Medina. first Al-Farabi had opinion that the main country is a country that conforms to the ideals of Islam. In Medina this is where the teachings of Islam are practiced perfectly, especially by following Islamic law both in the time of Prophet Muhammad and in the time of al-Khulafa al- Rasyidin. Second difficult to find the concept of country as exemplified by the Prophet Muhammad, the main ideal state.Keywords: Al-Farabi, State, and al-Madinah al-Fadhilah.